Enhancing sleep after training improves memory in down syndrome model mice. Issue 4 (7th October 2021) - Pittaras, Elsa; Colas, Damien; Chuluun, Bayara; Allocca, Giancarlo; Heller, Craig
Abstract: Down syndrome (DS) is a genetic disorder caused by the presence of all or part of the third copy of chromosome 21. DS is associated with cognitive disabilities, for which there are no drug therapies. In spite of significant behavioral and pharmacological efforts to treat cognitive disabilities, new and continued efforts are still necessary. Over 60% of children with DS are reported to have sleep apnea that disrupt normal sleep. Normal and adequate sleep is necessary to maintain optimal cognitive functions. Therefore, we asked whether improved quality and/or quantity of sleep could improve cognitive capacities of people with DS. To investigate this possibility, we used the Ts65Dn mouse model of DS and applied two methods for enhancing their sleep following training on mouse memory tasks. A behavioral method was to impose sleep deprivation prior to training resulting in sleep rebound following the training. A pharmacologic method, hypocretin receptor 2 antagonist, was used immediately after the training to enhance subsequent sleep knowing that hypocretin is involved in the maintenance of wake. Our behavioral method resulted in a sleep reorganization that decreased wake and increased rapid eye movement sleep following the training associated with an improvement of recognition memory and spatial memory in the DS model mice. Our pharmacologic approach decreased wake and increased non-rapid eye movement sleep and was associated with improvement only in the spatial memory task. These results show that enhancing sleep after the training in a memory task improves memory consolidation in a mouse model of DS.